N-(2-(1H-Indol-3-yl)ethyl)-2-(2-fluoro-[1,1′-biphenyl]-4-yl)propanamide - Stanimir Manolov; Iliyan Ivanov; Dimitar Bojilov (Molbank, 2020)
N-(2-(1H-Indol-3-yl)ethyl)-2-(2-fluoro-[1,1′-biphenyl]-4-yl)propanamide was prepared by a reaction between tryptamine and flurbiprofen, applying N,N’-Dicyclohexylcarbodiimide, as a coupling agent. The obtained new amide has a fragment similar to Brequinar, a compound used in SARS-CoV-2 treatment trials. The newly synthesized compound was fully analyzed and characterized via 1H, 13C-NMR, UV, IR, and mass spectral data.